Studies of neutron inelastic scattering in crystal and liquid scintillators - Bain, Cairns A R (Department of Physics, 2022)
An investigation has been made of the feasibility of using crystal, liquid and gel scintillators for the study of neutron inelastic scattering from elements, contained or loaded in the scintillators. The nuclides included those of iodine, cesium, lanthanum, holmium, praseodymium and bismuth. investigations showed that the technique was feasible for crystal and liquid scintillators, and indicated the study or 12 7I iri sodium iodide crystal to be the most suitable for further investigation. A study was then made of inelastic scattering to the 59 keV level of 1 2 7 I for incident neutrons in the energy range 60 to 360 keV. Cross section data obtained were compared with inelastic scattering cross sections calculated using a Hauser-Feshbach model of Auerbach and Moore. Experimental data were; found to be in reasonable agreement with the calculated cross sections based on neutron transmission coefficients given by Auerbach and Perey.